2017
DOI: 10.1007/s00198-017-4316-5
|View full text |Cite
|
Sign up to set email alerts
|

A randomized double-blind placebo-controlled trial of vitamin D supplementation in juvenile-onset systemic lupus erythematosus: positive effect on trabecular microarchitecture using HR-pQCT

Abstract: NCT01892748.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 40 publications
0
12
0
1
Order By: Relevance
“…Considering the role of vitamin D deficiency on the development of SLE, Yu et al ( 141 ) recently demonstrated that vitamin D plays a protective role in the autoantibody-induced injury of podocytes (kidney cells that wrap around capillaries of the glomerulus) in patients with lupus nephritis, which could be a potential novel therapeutic target to treat lupus nephritis. From a 24 week double-blind randomized placebo-controlled trial by Lima et al ( 142 ), it was established that supplementation of vitamin D in patients with juvenile-onset SLE effectively improved parameters of bone microarchitecture ( p = 0.024). Bone marrow mesenchymal stem cells from patients with SLE show impaired proliferative capacity compared with that of normal controls ( 143 ).…”
Section: Micronutrientsmentioning
confidence: 99%
“…Considering the role of vitamin D deficiency on the development of SLE, Yu et al ( 141 ) recently demonstrated that vitamin D plays a protective role in the autoantibody-induced injury of podocytes (kidney cells that wrap around capillaries of the glomerulus) in patients with lupus nephritis, which could be a potential novel therapeutic target to treat lupus nephritis. From a 24 week double-blind randomized placebo-controlled trial by Lima et al ( 142 ), it was established that supplementation of vitamin D in patients with juvenile-onset SLE effectively improved parameters of bone microarchitecture ( p = 0.024). Bone marrow mesenchymal stem cells from patients with SLE show impaired proliferative capacity compared with that of normal controls ( 143 ).…”
Section: Micronutrientsmentioning
confidence: 99%
“…The randomized, double-blind study showed that vitamin D supplementation (cholecalciferol 50,000 IU/ week for six months) in patients with juvenile lupus improved bone microarchitecture, with the tibia as parameter. Another advantage of this study was that the treatment of patients with vitamin D supplementation remained stable during the six months of follow-up, thus allowing a more accurate analysis of the effect of this supplementation on this rheumatic condition 18 .…”
Section: Chart 1: Characterization Of the Main Analyzed Studies Continuationmentioning
confidence: 99%
“…No significant changes were noted in the distal radius parameters, considering the coefficient of variation (CV) of HR-pQCT from our laboratory (distal tibia: density CV = 0.25%–1.16%, structure CV = 0.78%–6.35%; distal radius: density CV = 0.93%–1.41%, structure CV = 0.78%–6.35%) (Table 2). [17]…”
Section: Case Reportmentioning
confidence: 99%